Q = p(r+s)
--------------
(r+s) (r+s) Divide both sides by (r+s) so you can get the p bu itself this way you get q / (r+s) = p
We can add or subtract integer. We can also subtract like terms.
RS<span> ≅ </span><span>ST is the correct answer</span>
Answer:
![3(x+3)(x -1)](https://tex.z-dn.net/?f=3%28x%2B3%29%28x%20-1%29)
Step-by-step explanation:
![3x^2 + 6x -9](https://tex.z-dn.net/?f=3x%5E2%20%2B%206x%20-9)
All the terms in this polynomial are divisible by 3. Factor 3 out of this polynomial:
![= 3(x^2 + 2x -3)](https://tex.z-dn.net/?f=%3D%203%28x%5E2%20%2B%202x%20-3%29)
Now, factor inside the parentheses by grouping:
![= 3(x^2 -1x+3x -3)](https://tex.z-dn.net/?f=%3D%203%28x%5E2%20-1x%2B3x%20-3%29)
We knew to split the +2x up into -1x and 3x because -1 and 3 multiply to get -3, which is the last value in the polynomial.
![= 3(x(x -1)+3(x -1))\\= 3(x+3)(x -1)](https://tex.z-dn.net/?f=%3D%203%28x%28x%20-1%29%2B3%28x%20-1%29%29%5C%5C%3D%203%28x%2B3%29%28x%20-1%29)
Therefore, the final factored polynomial is
.